Short-term efficacy of eye-saving treatment for medium and large T1-T4 choroidal melanomas in Ukrainian population as assessed by local tumor control (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To assess the efficacy of eye-saving treatment (involving transpupillary thermotherapy (TTT) combined with strontium-90 (Sr90)/ yttrium-90 (Yt90) brachytherapy (BT)) for medium and large CM in terms of local tumor control rate at 12 months after the initiation of treatment.Material and Methods: This retrospective cohort study included 283 patients with CM who were treated at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine” from 2007 to 2024. The study sample consisted of 125 men (44.2%) and 158 women (55.8%), with a mean age (standard deviation) of 54.2 (12.4) years. Short-term success was defined as evidence of complete tumor regression, partial tumor regression or stabilization of the tumor process at 12 months after the initiation of treatment. Short-term failure was defined as evidence of continued tumor growth, tumor recurrence (a tumor growing from the scar) or extrabulbar spread at 12 months after the initiation of treatment.Results: Short-term treatment success was achieved in 274 patients (96.8%). Particularly, complete tumor regression was achieved in 86/274 patients (31.4%) or 86/283 patients (30.4%), partial tumor regression, in 165/274 (60.3%) or 165/283 (58.3%), and regression with stabilization of tumor size, in 23/274 (8.4%) or 23/283 (8.1%). Local treatment failure in the form of continued tumor growth was seen in 9/283 patients (3.2%) and led to enucleation.Conclusion: More effective outcome of the eye-saving treatment (involving TTT combined with Sr90/ Yt90 BT) for CM may be expected in patients with T1 stage (tumor thickness of 3.1-6.0 mm and base diameter of 3.1-9.0 mm), T2 stage (3.1-9.0 mm; 3.1-15.0 mm), and T3 stage with category 4 tumor size (tumor thickness of 3.1-6.0 mm and base diameter of 15.1-18.0 mm) and category 5 tumor size (6.1-9.0 mm; 12.1-18.0 mm).
Keywords: melanoma; choroidal melanoma; laser treatment; ophthalmology; oncology; ionizing radiation; radiation therapy